2022
DOI: 10.1007/s00408-022-00574-7
|View full text |Cite
|
Sign up to set email alerts
|

Poly I:C Exacerbates Airway Inflammation and Remodeling in Cigarette Smoke-Exposed Mice

Abstract: Background Chronic obstructive pulmonary disease (COPD) is a chronic respiratory disorder characterized by chronic inflammation and airway remodeling. Cigarette smoke (CS) and respiratory viruses are major causes of COPD development and exacerbation, but the mechanisms of these compounding factors on inflammation and pathological changes in airway structure still need further investigation. Purpose This work aimed to investigate the effects and mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Smoking also causes oxidative stress and inflammatory activities in the lung, affecting airway permeability (leaky lung) and angiotensin-converting enzyme 2 (ACE2) expression. 8 The ACE2 receptor is the site of SARS-CoV2 virus entry into the host cell, since the S2 domain of the viral spiked envelope has a high affinity for the receptor. It is shown that smoking up regulates ACE-2 receptor in the lung epithelium.…”
Section: Smokingmentioning
confidence: 99%
“…Smoking also causes oxidative stress and inflammatory activities in the lung, affecting airway permeability (leaky lung) and angiotensin-converting enzyme 2 (ACE2) expression. 8 The ACE2 receptor is the site of SARS-CoV2 virus entry into the host cell, since the S2 domain of the viral spiked envelope has a high affinity for the receptor. It is shown that smoking up regulates ACE-2 receptor in the lung epithelium.…”
Section: Smokingmentioning
confidence: 99%
“…In conclusion, viral infections may potentiate cigarette smoke-induced injury and significantly prolong inflammation and airway remodeling, even after smoking cessation. The paper by Li et al ( 8 ) supports that viral infections in COPD patients can cause more than just a temporary setback. Perhaps it is time to focus more on the COPD lung virome and find ways to monitor and treat viral infections in these patients, in order to give their lungs a chance to heal.…”
mentioning
confidence: 99%
“…Much less is known about the potential chronic impact of recurrent viral infections in COPD development and persistence. This gap is addressed by the work of Li et al, in this issue of LUNG [ 8 ]. The authors utilize a cigarette smoke/immune activation (through poly-I:C administration) model, to demonstrate that combination exposure exacerbates inflammatory and remodeling changes beyond what either exposure alone achieves.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of obstructive airway disease comprised a significant portion of articles published is 2022. Clinical studies of COPD examined diagnosis [ 2 ], risk factors [ 3 ], predictors of outcomes [ 4 9 ], and therapeutic interventions [ 10 , 11 ], whereas preclinical investigations evaluated chronic cigarette smoke-induced inflammation and airway remodeling [ 12 , 13 ]. Contributions in the field of asthma included physiological studies [ 14 18 ], effects of therapeutic interventions [ 19 ], social determinants of clinical outcomes [ 20 ], asthma-associated cough [ 21 , 22 ] and preclinical investigations [ 23 ].…”
mentioning
confidence: 99%